Spontaneous hemothorax in neurofibromatosis type 1: a rare case of intercostal artery aneurysm rupture and the role of permissive hypotension - Salama, Moataz Ahmed; Al Hammadi, Asmaa; Osman, Yousif (International Surgery Journal, 2025)
This case report presents the effective management of a rare and life-threatening spontaneous hemothorax resulting from the rupture of an intercostal artery aneurysm in a patient with undiagnosed neurofibromatosis type 1 (NF-1). The patient exhibited acute chest pain and hemodynamic instability, requiring a multidisciplinary strategy that included permissive hypotension and interventional radiology (IR). Coil embolization successfully managed the hemorrhage, resulting in hemodynamic stabilization and positive patient outcomes. This case highlights the significance of promptly identifying spontaneous hemothorax in NF-1, the necessity of targeted resuscitation strategies, and the effectiveness of minimally invasive endovascular techniques in addressing vascular complications. This case study highlights the complexities involved in addressing an atypical presentation of an undiagnosed case of NF-1, which was further complicated by a sudden spontaneous hemothorax resulting from the abrupt rupture of an intercostal artery aneurysm. This underscores the essential importance of promptly identifying life-threatening bleeding and the necessity for a resuscitation strategy that is customized to the individual patient. Additionally, it highlights the benefits of employing a permissive hypotension protocol in stabilizing the patient’s hemodynamics and preventing exacerbation of bleeding. The conclusive management utilizing coil embolization through IR effectively accomplished hemostasis. This paper aims to demonstrate that an emergency medicine physician must consider uncommon differential diagnoses when faced with a patient presenting with chest pain. It is crucial to maintain a high level of suspicion for rare, life-threatening conditions, including neurofibromatosis.